(untitled) (Journal of Economic Research & Business Administration, 2019)
The articles reveal a different interpretation of the concept of “human resources” at the interstate and regional levels, and in scientific research. The lack of a unified approach complicates the application of programs to improve the competitiveness of the region and reduces their effectiveness. Human resources are a key factor in the economic and social development of the region. They act as a tool for the implementation of priority areas of development of the region. The effectiveness of such implementation depends largely on the compliance of the qualification of the population with the requirements of the specifics of the economy of the region. Given the interrelationship of socio-economic policy elements, it can be noted that human resource development is influenced by various sectors of the economy, including health and education. In the article, the authors conducted an expert assessment in the field of human resources in improving the competitiveness of the region. When evaluating proposals to improve the quality of education, we use a multidimensional problem of choosing the most optimal option. With the help of the questionnaire, the most appropriate solutions to improve the quality of educational services were selected. Thus, the authors define the methods of expert evaluation, in particular, the Delphic method as an ideal tool for predicting measures to improve the competitiveness of the region by achieving an optimal balance of supply and demand for human resources.